English learning using movement and song at TPP AL Firdaus Surakarta - Saputri, Lutfiana Ramadhania; Widyasari, Choiriyah (Universitas Muhammadiyah Surakarta, 2024)
The total number of words in the abstract should not exceed 250 words. This article aims to explore effective methods and strategies in improving early childhood English skills, with a focus on the application of movement and song methods in TPP AL Firdaus Surakarta. This study uses a qualitative approach with direct observation and interviews. Data was collected through observation of teaching and learning activities in the classroom, as well as interviews with teachers and parents. Observation was focused on the application of the movement and song method in English learning and children's responses to the method. Data analysis was carried out descriptively to identify the impact and effectiveness of this method in improving children's English language skills. The results showed that the movement and song methods significantly increased children's motivation, curiosity, and enthusiasm in learning English. Children are able to remember new vocabulary better through the repetition of words in songs and movements. This activity also improves children's motor skills and collaboration when doing movements together. In addition, the use of audio-visual media such as videos and picture cards enriches children's learning experience, helping them recognize and pronounce words in English better. Teachers at TPP AL Firdaus Surakarta have succeeded in creating a fun and interactive learning atmosphere, which motivates children to be more active in the learning process. This research makes an original contribution to the understanding of the importance of movement and song methods in English language learning for early childhood. The results of this study can be a reference for educators at TPP AL Firdaus and other educational institutions in developing more effective and fun teaching strategies for children. This research also highlights the important role of teachers and the school environment in supporting children's language development, as well as the importance of parental support in the learning process.